ANALYZING THE EFFECTIVENESS OF ICT MODELS IN TEACHER EDUCATION AS PER NEP-2020 - Dr. Manoj Kumar (International Educational Journal of Science and Engineering, 2026)
The study examines the effectiveness of ICT models in teacher education within the framework of India’s National Education Policy (NEP) 2020. As digital transformation reshapes global education, ICT has become central to enhancing teacher preparedness, instructional quality and professional competence. The paper highlights NEP-2020’s emphasis on digital infrastructure, multilingual e-content, teacher capacity building, blended learning and the establishment of NETF to promote the integration of technology in education. Various ICT models Blended Learning, Flipped Classroom, TPACK, SAMR, LMS-based instruction, Virtual Classrooms and Open Educational Resources (OER) are analyzed in terms of their pedagogical strengths and implementation challenges. Comparative evaluation reveals that while blended and flipped approaches enhance active learning, models like TPACK and SAMR support deeper integration of technology with content and pedagogy. LMS platforms such as DIKSHA and SWAYAM further promote structured learning pathways and analytics-based progress tracking. The findings indicate that ICT models significantly enhance teacher competencies, including digital literacy, instructional design skills and assessment proficiency. Evidence shows improved student engagement, better learning outcomes and increased teacher confidence when technology-supported pedagogies are systematically adopted. The study also notes major challenges: digital divide, insufficient training, infrastructure gaps, language barriers and resistance to change. To strengthen ICT implementation, the paper recommends continuous professional development, better digital infrastructure, multilingual content creation, public–private partnerships and strong monitoring mechanisms. The study concludes that ICT-enabled teacher education, aligned with NEP-2020, is essential for building a future-ready teaching workforce capable of navigating technologically enriched learning environments.